The New Russian Nationalism: Imperialism, Ethnicity and Authoritarianism 2000-2015 - Rachael Horwirtz (Slovo, 2017)
This useful and timely volume covers the growth of Russian nationalism from 2000 to 2015. It was in the process of completion during the annexation of Crimea in March 2014 and thus most of the chapters refer largely to events prior to that date, with some analytical coverage of how Russian nationalism has shaped public opinion of the annexation and subsequent Eastern Ukrainian conflict. It is thoroughly researched and yet accessible to the general reader, though with a few minor issues. Read here.